The First Report on Excellent Cycling Stability and Superior Rate Capability of Na3V2(PO4)3 for Sodium Ion Batteries. Issue 4 (29th November 2012) - Saravanan, Kuppan; Mason, Chad W.; Rudola, Ashish; Wong, Kim Hai; Balaya, Palani
Abstract Sodium ion batteries are attractive for the rapidly emerging large‐scale energy storage market for intermittent renewable resources. Currently a viable cathode material does not exist for practical non‐aqueous sodium ion battery applications. Here we disclose a high performance, durable electrode material based on the 3D NASICON framework. Porous Na3V2(PO4)3/C was synthesized using a novel solution‐based approach. This material, as a cathode, is capable of delivering an energy storage capacity of ∼400 mWh/g vs. sodium metal. Furthermore, at high current rates (10, 20 and 40 C), it displayed remarkable capacity retention. Equally impressive is the long term cycle life. Nearly 50% of the initial capacity was retained after 30, 000 charge/discharge cycles at 40 C (4.7 A/g). Notably, coulombic efficiency was 99.68% (average) over the course of cycling. To the best of our knowledge, the combination of high energy density, high power density and ultra long cycle life demonstrated here has never been reported before for sodium ion batteries. We believe our findings will have profound implications for developing large‐scale energy storage systems for renewable energy sources.